Anchoring and overconfidence: The influence of culture and cognitive abilities - Monika Czerwonka (International Journal of Management and Economics, 2017)
Anchoring and overconfidence are some of the best-known biases in psychology and behavioral finance literature. While a number of studies have investigated the evidence of these biases and explored the motives and human factors that contribute to the one's susceptibility to the effects, little is known about the cultural factors behind these heuristic biases. This paper aims to fill the research gap and shows the differences in proneness to the anchoring effect and overconfidence in two samples of students from Poland and India. The purpose of the study is twofold: to analyze susceptibility to behavioral effects relative to cultural background; and to consider the subjects' cognitive abilities as a potential factor in their exposure to behavioral biases and confirm that subjects with higher cognitive skills, measured by the cognitive reflection test (CRT) display less susceptibility to the above heuristic biases.
Keywords: G02; C91; 650; anchoring; overconfidence; culture; cognitive reflection test